Conservation agriculture based crop management practices impact diversity and population dynamics of the insect-pests and their natural enemies in agroecosystems - Jasrotia, Poonam; Kumari, Pritam; Malik, Kapil; Kashyap, Prem Lal; Kumar, Sudheer; Bhardwaj, Ajay Kumar; Singh, Gyanendra Pratap (Frontiers in Sustainable Food Systems, 2023)
Human efforts to grow abundant food through the persistent use of resource-intensive farming practices have resulted in declining soil health and deterioration of ecosystem functions and services. Conservation agriculture (CA) has emerged as a practice to minimize the impacts of conventional resource-exhaustive and energy-intensive agriculture. Minimum soil disturbance, permanent soil cover, and diversification are key components of CA. The conventional techniques have also evolved to counter constraints that existed or to harvest newly emerged opportunities. Though CA may bring in benefits in terms of soil and water conservation, the consequent changes in moisture and temperature regimes due to reduced tillage and surface cover would influence biological activity, including insect pests and their natural enemies which dwell within these agroecosystems. The changed conditions may favour particular insect communities and their ecological niches. Recent insect-pest outbreaks in North-Western India and imbalances reported in Indo-Gangetic Plains point to the need for a better understanding of the inter-relationships between tillage intensity, residue retention, and insect pest population dynamics. The current review analyzes the existing state of knowledge of these dynamics and presents the scenarios that may emerge as CA get more acceptance. The meta-analysis would help to develop a countermeasure to improve performance and ecosystem services.